Intelligent automatic door lock - Abdul Rahim, Herlina (Universiti Teknologi Malaysia, 2007)
This project is mainly purposed to produce a based micro controller MC68HC11 system for house security with the help of remote control, which is our hand phone. This system is build based on DTMF signal produced by the hand phone. All user has to do is only dial a number to which this system is attached and push certain digits on the hand phone’s keypad to activate the system. By activating the system, the door will be opened due to correct password. While, the wrong password inserted by user will abandoned by the system. This project is actually has a bright future and this encourage the implementation of this project as to produce a security system and ease human’s life.